New heteroleptic lanthanide complexes as multimodal drugs: Cytotoxicity studies, apoptosis, cell cycle analysis, DNA interactions, and protein binding. (18th October 2020) - Munteanu, Alexandra‐Cristina; Musat, Mihaela Georgiana; Mihaila, Mirela; Badea, Mihaela; Olar, Rodica; Nitulescu, George Mihai; Rădulescu, Flavian Ștefan; Brasoveanu, Lorelei Irina; Uivarosi, Valentina
Abstract : We report herein the synthesis and characterization of four new heteroleptic complexes of Sm(III), Eu(III), Gd(III), and Tb(III) with the natural flavonoid 5‐hydroxyflavone (primuletin) and 1, 10‐phenanthroline. According to the physicochemical characterization, the mononuclear complexes correspond to the general formula [Ln(OH) 2 L 1 L 2 ]· n H 2 O, where L1 = C15 H9 O3 (deprotonated 5‐hydroxyflavone) and L2 = C12 H8 N2 (1, 10‐phenanthroline), Ln is the lanthanide cation, and n = 4 for Sm(III), 3.5 for Eu(III), 2 for Gd(III), and 3 for Tb(III). A six‐coordinated distorted octahedron geometry was proposed for the complexes, and density functional theory (DFT) studies were used to calculate their optimized geometry. Cytotoxicity was studied using MTS assay on cervical, colorectal, colon, breast, and ovarian adenocarcinoma cell lines. Flow cytometry data were consistent with apoptotic cell death and disruption of the cell cycle in cervical and colon cancer cells. As a means to investigate the mechanism underlying the cytotoxic effects, the abilities of the complexes to interact with calf thymus DNA, human serum albumin, and transferrin have also been assessed. According to experimental and computational studies, the four lanthanide complexes act as DNA intercalators and bind strongly to serum proteins. Abstract : Heteroleptic complexes of Sm(III), Eu(III), Gd(III), and Tb(III) with 5‐hydroxyflavone and 1, 10‐phenanthroline have been synthesized and characterized; DFT studies have been used to calculate their optimized geometry. The complexes were found to be cytotoxic on several cancer cell lines, to induce apoptosis and act as cell cycle modulators in cervix and colon adenocarcinoma cells. All four complexes act as DNA intercalators and bind strongly to serum proteins.